Pengaruh Kualitas Pelayanan, Kepuasan Nasabah Terhadap Loyalitas Nasabah dan Biaya Sebagai Variabel Intervening di Koperasi Baitul Maal Wa Tamwil Usaha Gabungan Terpadu Nusantara di Kota Samarinda - Angelita, Sarah; Mahrus, Moh; Yuliani, Irma (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Customer value creates a company and how good customer value can provide customer satisfaction. And sustainable customer satisfaction can be achieved through customer value which must be continuously maintained or improved. With these efforts, it is hoped that customer loyalty itself, by increasing sustainable customer loyalty, can be fostered through the company's own strategy. Then the quality of service provided also greatly influences customer loyalty, by providing good service and according to customer expectations. And costs are also one of the factors that influence loyalty towards a company or agency. So this research aims to find out whether good service and customer satisfaction and also the costs provided by the cooperative can influence loyalty in Baitul Maal Wa Tamwil Usaha Usaha Bersama Terpadu Nusantara (BMT UGT NUSANTARA). The type of research used in this research is associative with quantitative data collection methods. Based on the calculation results, service quality has a simultaneous effect on customer loyalty, then satisfaction has a significant effect on loyalty, while service quality and satisfaction have a simultaneous effect on costs, while service quality has a significant effect on customer loyalty through costs. And customer satisfaction with loyalty through costs does not have a significant effect on customer loyalty. Keywords: Quality of service, customer satisfaction, costs, customer loyalty, sharia cooperatives